The traveller from the heavens - Khan, Nafees (Goodword Books India, 2002)
"The Traveler from the Heavens" tells the story of a celestial being or traveler who descends to Earth, often to share wisdom or insights about life and the universe. The narrative typically explores themes of spirituality, human connection, and the importance of understanding one's purpose. Through encounters with people, the traveler imparts lessons on kindness, compassion, and the pursuit of knowledge, encouraging readers to reflect on their own journeys and the impact they can have on others.